The Role Of Asean Intergovernmental Commision On Human Right (AICHR) On Handling Of Human Trafficking In Indonesia - Wincent Anggadha (International Journal on Social Science, Economics and Art, 2020)
The issue of human trafficking is now more pronounced as the government's efforts to eradicate crime are considered to be minimal and less effective. Protection of citizens is absolutely essential because it is a state obligation, but besides that there needs to be cooperation between non-state actors in international world to guarantee the creation of human security. Due to the large number of human trafficking cases in Southeast Asia, encouraging ASEAN countries to establish ASEAN Intergovernmental Commission on Human Rights (AICHR) in 2009 in Cambodia. Therefore, this study aims to determine the basis of the establishment of ASEAN Intergovernmental Commission on Human Rights (AICHR), and to know the role of ASEAN Intergovernmental Commission on Human Rights (AIHCR) on the handling of trafficking in Indonesia. The research was conducted by using qualitative method with normative approach. The results show that AICHR was formed with six main objectives: 1) Promoting and protecting human rights and the right of freedom of ASEAN nation. 2) To uphold ASEAN peoples' right to live in peace, dignity and prosperity, 3) To realize the objectives of ASEAN organizations as stipulated in the Charter: to maintain stability and harmony in the region while maintaining friendship and cooperation among ASEAN members; 4) Promoting human rights in At the regional level while maintaining the characteristics, historical, cultural and religious differences of each country, as well as maintaining a balance of rights and obligations, 5) Promoting regional cooperation through complementary national and international efforts to promote and protect human rights; ) Upholding the international human rights principles embodied in the Universal Declaration of Human Rights, the Vienna Declaration and its implementation program, and other human rights instruments, in which ASEAN members are parties. The role of AICHR in the handling of human trafficking is to conduct consultation, coordination and collaboration with all 3 ASEAN communities: 1) ASEAN Political and Security Community, 2) ASEAN Economic Community, and 3) ASEAN Socio-Cultural Community.